The absence of myristic acid decreases membrane binding of p60src but does not affect tyrosine protein kinase activity. - Buss, J E (1986)
We have constructed two point mutants of Rous sarcoma virus in which the amino-terminal glycine residue of the transforming protein, p60src, was changed to an alanine or a glutamic acid residue. Both mutant proteins failed to become myristylated and, more importantly, no longer transformed cells. The lack of transformation could not be attributed to defects in the catalytic activity of the mutant p60src proteins. In vitro phosphorylation of the peptide angiotensin or of the cellular substrate proteins enolase and p36 revealed no significant differences in the Km or specific activity of the mutant and wild-type p60src proteins. However, when cellular fractions were prepared, less than 12% of the nonmyristylated p60src proteins was bound to membranes. In contrast, more than 82% of the wild-type protein was associated with membranes. Wild-type p60src was phosphorylated by protein kinase C, a protein kinase which associates with membranes when activated. The mutant proteins were not. This finding supports the idea that within the intact cell the nonmyristylated p60src proteins are cytoplasmic and suggests that this apparent solubility is not an artifact of the cell fractionation procedure. The myristyl groups of p60src apparently encourages a tight association between protein and membranes and, by determining the cellular location of the enzyme, allows transformation to occur.